Stroboscopy: an evolving tool for voice analysis in vocal cord pathologies - Rajput, Sneha D.; Poriya, Mittal J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Benign vocal fold disease, such as vocal polyp, vocal nodule, intracordal cyst or Reinke’s edema is one of the most common causes which deteriorate the voice. Since 1854 when Manuel Garcia first observed the movement of his own vocal cords using a laryngeal mirror and sunlight as the light source, a number of techniques for demonstrating laryngeal anatomy have evolved. Preoperative evaluation of these lesions initially by indirect laryngoscopy or direct rigid laryngoscopy, gave way to the use of transnasal flexible fibreoptic endoscopy in the eighties. The introduction of the video stroboscope into Otorhinolaryngology practice has revolutionized the assessment of vocal cord pathology. Methods: The present study includes a 50 cases of subjects with complain of change of voice coming at department of E.N.T and Head and Neck surgery, at our hospital. A detailed history was taken following which a thorough examination of larynx using appropriate techniques were carried out. Further investigations were done as and when required. Results: On stroboscopic examination patients were analyzed on four parameters like, symmetry, amplitude, periodicity and mucosal wave. Observations of periodicity and mucosal wave were significantly different in preoperative and post-operative analysis. Stroboscopic evaluation suggested that preoperatively 50% of the patient were having asymmetricity, decreased amplitude, aperiodicity and absent mucosal wave. On postoperative follow-up at 15 days and 2 months interval almost all the patients got all the parameters near normal. Conclusions: It was observed that statistical significant difference in pre and postoperative findings of different parameters of voice evaluated using it. We can draw the probable conclusion that video stroboscope proved to be useful and reliable tool for evaluation of the patients with benign vocal cord pathologies as it reflects the change in the all the parameters of voice postoperatively most accurately and promptly.